Expression Patterns of Microenvironmental Factors and Tenascin-C at the Invasive Front of Stage II and III Colorectal Cancer: Novel Tumor Prognostic Markers - Hashimoto, Mai; Uesugi, Noriyuki; Osakabe, Mitsumasa; Yanagawa, Naoki; Otsuka, Koki; Kajiwara, Yoshiki; Ueno, Hideki; Sasaki, Akira; Sugai, Tamotsu (Frontiers in Oncology, 2021)
Background Biological markers expressed in cancer cells and the surrounding cancer-associated fibroblasts (CAF) can be used for prediction of patient prognosis in colorectal cancer (CRC). Here, we used immunohistochemical techniques to evaluate cancer cells’ expression of specific biomarkers that are closely associated with neoplastic progression. Methods Immunohistochemical markers included Ki-67, p53, β-catenin, MMP7, E-cadherin and HIF1-α. We also characterized microenvironmental markers expressed by CAF, including expression of α-smooth muscle actin, CD10, podoplanin, fibroblast specific protein 1, platelet derived growth factor β, fibroblast association protein, tenascin-C (TNC), ZEB1 and TWIST1. The study population consisted of 286 CRC patients with stage II and III disease. Stage II and III CRC were divided into a first and a second cohort (for validation). The CRCs were stratified using cluster analysis. To identify the utility of prognostic markers in stage II and III CRC, univariate and multivariate analyses were performed in both cohorts. Results Stage II and III CRCs were stratified into 3 subgroups. Specific subgroups were significantly correlated to disease-free survival using univariate and multivariate analyses in the first cohort. High expression of TNC was identified as a single prognostic marker in both cohorts by univariate and multivariate analyses. Conclusions We suggest that the presence of a specific subgroup defined by multiple markers can be used for prediction of CRC outcome in stages II and III. In addition, we showed that high expression of TNC was correlated with a poorer prognosis in stages II and III of CRC.